Preparation and Characterization of Magnetite Nanoparticles Combined with Polyaniline and Activated Carbon. Issue 1 (May 2019) - Intan Subadra, ST. Ulfawanti; Sutiami, Rita; Taufiq, Ahmad; Diantoro, Markus; Sunaryono; Arif; Hidayat; Mufti, Nandang; Hidayat, Nurul; Susanto, Hendra; Ari Adi, Wisnu
Abstract: In this paper, we report the preparation of magnetite nanoparticles combined with polyaniline and activated carbon. The results of the X-Ray diffraction data analysis showed that the samples had a magnetite crystal phase without other phases. The existence of polyaniline and activated carbon was confirmed using Fourier transform infrared spectroscopy characterization shown by the presence of S=O, C-N, and C-C. The sample of synthesis results in this work had the band gap of 3.23 eV. Moreover, the results of data analysis using vector network analyzer revealed the maximum reflection loss value of -14 with the absorbance of 50%. Thereby, the synthesis optimization needs to be done to increase the sample absorbance to the radar wave.